The THE-QS World University Rankings, 2004 - 2009 - Richard Holmes (UiTM Publisher, 2010)
This paper reviews the origin, development and demise of the Times Higher Education Supplement (now Times Higher Education) - QS Quacquarelli Symonds (QS) World University Rankings between 2004 and 2009. It describes the structure and methodology of the rankings, their public impact and various criticisms that have been made. It also analyses changes that were introduced between 2005 and 2009 and concludes by noting the development of two distinct ranking systems by the magazine Times Higher Education (THE) and by its former partner, the consulting company Quacquarelli Symonds.